2008
DOI: 10.1093/cercor/bhn065
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissociation in Right Inferior Frontal Cortex during Performance of Go/No-Go Task

Abstract: The contribution of the right inferior frontal cortex to response inhibition has been demonstrated by previous studies of neuropsychology, electrophysiology, and neuroimaging. The inferior frontal cortex is also known to be activated during processing of infrequent stimuli such as stimulus-driven attention. Response inhibition has most often been investigated using the go/no-go task, and the no-go trials are usually given infrequently to enhance prepotent response tendency. Thus, it has not been clarified whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

45
232
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 250 publications
(278 citation statements)
references
References 55 publications
45
232
1
Order By: Relevance
“…confounding inhibitory demands with attentional capture because of low no-go stimulus frequency (Chikazoe et al, 2009a;Criaud and Boulinguez, 2013). Interestingly, the contrast correct no-go4incorrect no-go showed no significant pharmacogenetic effect at the chosen level of statistical significance.…”
Section: Pharmacogenetic Findingsmentioning
confidence: 88%
See 4 more Smart Citations
“…confounding inhibitory demands with attentional capture because of low no-go stimulus frequency (Chikazoe et al, 2009a;Criaud and Boulinguez, 2013). Interestingly, the contrast correct no-go4incorrect no-go showed no significant pharmacogenetic effect at the chosen level of statistical significance.…”
Section: Pharmacogenetic Findingsmentioning
confidence: 88%
“…Using the most stringent contrast to isolate inhibitory mechanisms in the Go/No-Go task (correct no-go4correct odd) (Chikazoe et al, 2009a), we found an interaction between SLC6A3 genotype and drug condition for BOLD during successful inhibition. The interaction indicated a BOLD increase with MPH in 9R carriers, but a decrease in 10/10 homozygotes.…”
Section: Pharmacogenetic Findingsmentioning
confidence: 91%
See 3 more Smart Citations